Active Self-Assembled Monolayer Sensors for Trace Explosive Detection - Li, Mingliang (Langmuir : the ACS journal of surfaces and colloids, 2020)
Trace explosives can be detected with the help of a portable device using a flexible active self-assembled monolayer (SAM). 9,10-diphenyl anthracene with aggregation-induced emission enhancement (AIEE) properties is selected as the fluorophore. Phosphoric acid as the anchor group is linked to the fluorophore through an alkyl chain and able to self-assemble into a dense monolayer on the HfO2 adhesion layer on a flexible substrate. The dense SAMs show high fluorescence intensity, which can be quenched by nitroaromatic compounds (NACs), and have advantages of high response rate, sensitivity, reversibility, and selectivity